2018
DOI: 10.3390/molecules23081848
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of the Liver, Kidney, and Spleen of Mice Exposed to Gold Nanoparticles

Abstract: Gold nanoparticles (GNPs) are biocompatible nanomaterials that are currently researched for biomedical applications such as imaging and targeted drug delivery. In this investigation, we studied the effects of a single dose (injected on day 1) as well as a priming dose (two injections with a gap of one week) of 5 nm, 20 nm, and 50 nm diameter GNPs on the structural and biochemical changes in the liver, kidney, and spleen of mice. The results showed that small sized GNPs (5 nm) produced significant pathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
79
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(98 citation statements)
references
References 47 publications
18
79
1
Order By: Relevance
“…Although Ibrahim et al reported some pathological changes in the kidney after exposure to AuNPs during work, such as alterations in glomeruli, dilated tubules, oedema exudate, mild necrosis, and infiltration of inflammatory cells; these pathological changes were considered minimal and insignificant in the kidneys, regardless of the size of the AuNPs [184].…”
Section: Nephrotoxicitymentioning
confidence: 99%
“…Although Ibrahim et al reported some pathological changes in the kidney after exposure to AuNPs during work, such as alterations in glomeruli, dilated tubules, oedema exudate, mild necrosis, and infiltration of inflammatory cells; these pathological changes were considered minimal and insignificant in the kidneys, regardless of the size of the AuNPs [184].…”
Section: Nephrotoxicitymentioning
confidence: 99%
“…Once fixed tissue fragments were passed through increasing concentrations of alcohol solutions (70%, 95%, absolute) for dehydratation, cleared using xylene as clearing agent and embedded into paraffin blocks in a tissue processor (Leica TP-20, Leica Microsystems, Wetzlar, Germany). All tissue processing was done according to Ibrahim et al (2018). Morphometric evaluation of the villi length and crypt depth was carried out using a computerassisted microscopic image analysis system.…”
Section: Histo-morphometric Analysismentioning
confidence: 99%
“…1 Nevertheless, NPs with a size ranged of 20-50 nm are considered appropriate application involving drug delivery. 39 NPs with a size less than 20 nm (eg 10 nm) have been shown to accumulate in the liver and spleen of rats, 40 while NPs of larger size (20-100 nm) have been found to accumulate in the kidney. 41 On the other hand, NPs with a size less than 20 nm could be rapidly cleared by the kidneys, 42,43 while larger NiNPs may be difficult to be uptaken by cells.…”
Section: Discussionmentioning
confidence: 99%